Mobile Medical Apps for Pharmacy and Drug Reference. Issue 2 (3rd July 2021) - Stuart, Daniel
Abstract: Libraries play a key role in providing drug information resources. While traditional databases and clinical search engines offer pharmacy-related tools for practitioners, more discipline-specific resources on mobile-friendly platforms have emerged as options for use at the point of care. This review identifies a select number of drug and pharmacy mobile apps best supported through libraries to serve clinicians and educators.